Association of Vitamin D Deficiency with Postnatal Respiratory Distress in Newborns - Birgül Say; Mehmet Yekta Öncel; Nurdan Uraş (Galenos Publishing House, 2019)
INTRODUCTION: Respiratory distress is one of the common causes of admission in the early neonatal period with transient tachypnea of newborn (TTN) as the commonest cause which resolves in the first three days of life. The aim of this study was to investigate the effects of serum 25 hydroxy vitamin D (25 (OH) D) levels on the causes of TTN and non-TTN. METHODS: This case-control study was conducted in neonatal intensive care unit of the Zekai Tahir Burak Maternity Teaching Hospital in Turkey. We enrolled 58 neonates with gestational age of ≥36 weeks whom were postnatal respiratory distress. Serum 25 (OH) D levels were measured immediately after birth of the neonate and clinical, laboratory and radiological findings were evaluated and diagnosed. RESULTS: The study population included a total of 58 (34 boys, 24 girls) neonate. Among the 36 patients with respiratory distress, 24 (66%) of them had TTN, 12 (34%) of them had non-TTN respiratory distress causes (neonatal pneumonia, pneumothorax and meconium aspiration syndrome). Of these infants, 31 (53.4 %) had cord blood 25(OH)D levels ≤5 ng/mL (group 1), 17 (29.3 % ) had 25(OH) D levels 5-15 ng/mL (group 2), 10 (17.2% ) had 25(OH) D levels >15 ng/mL (group 3). DISCUSSION AND CONCLUSION: As a result, it was observed that in children, serum vitamin D deficiency did not a risk for TTN and non-TTN respiratory distress causes. The well designed studies are needed to prove whether the level of 25 (OH) D vitamin is associated with respiratory distress in the postnatal period.